Emigration als literarisches Verfahren bei Zinovij Zinik - Pülsch, Anja (Slavistische Beitraege, 1995)
Zinovij Zinik emigrated in the 70s from the Soviet Union via Israel to the United Kingdom, where he settled in London. The topic of the present work is based on an essay by Zinik titled "Emigracija kak literaturnyj priem" ("Emigration as a Literary Process"), in which he himself reflects on the importance of voluntary exile for his work.